The Effect of Sharia Financial Literacy on Millenials' Investment Decisions - Fitria Husnatarina (Pt. Anagata Sembagi Education, 2025)
This study examines the effect of Sharia financial literacy on millennials’ investment decisions by conducting a Systematic Literature Review of 88 empirical studies published between 2013 and 2024. Findings show that Sharia financial literacy significantly shapes millennials’ ethical-risk balancing, cognitive filtering of compliance claims, digital investment navigation, and correction of behavioral biases such as overconfidence and herding. The review identifies several behavioral mechanisms through which literacy influences investment decisions, including improved verification of Sharia compliance, enhanced portfolio rationality, and stronger intention behavior alignment. The impact of literacy, however, is moderated by contextual factors such as digital platform transparency, regulatory clarity, social influence, religiosity, socioeconomic capacity, and psychological readiness. These moderators determine whether literacy translates into consistent and informed ethical investment behavior. The study concludes that increasing Sharia financial literacy is necessary but not sufficient; it must be supported by enabling institutional and digital ecosystems to effectively guide millennials toward rational and compliant investment choices.